2014
DOI: 10.1007/s00417-014-2733-0
|View full text |Cite
|
Sign up to set email alerts
|

A new kind of labyrinth-like capillary is responsible for leakage from human choroidal neovascular endothelium, as investigated by high-resolution electron microscopy

Abstract: A newly discovered type of pathological capillary, called a labyrinth capillary, is very likely responsible for the permanent leakage of fluid. Due to the small vessel lumen, thrombocytes cannot enter these capillaries to close the leakages. Fenestrations did not appear to play a significant role in vascular leakiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
4
4
0
Order By: Relevance
“…Few fenestrations in the endothelium were observed in the CNV vessels of this CNV rat model ( Fig. 4 3E), which correlates with the low number of endothelial fenestrations in human CNV (Biesemeier et al, 2014, Schraermeyer et al, 2015. Hofman's group indicated that the vessel leakage was not caused by the fenestration formation, but was due to the increased active pinocytotic vesicles in the endothelia of CNV vessels (Hofman et al, 2000).…”
Section: Overexpression Of Vegf Leads To the Hyperpermeability Of Thesupporting
confidence: 52%
See 3 more Smart Citations
“…Few fenestrations in the endothelium were observed in the CNV vessels of this CNV rat model ( Fig. 4 3E), which correlates with the low number of endothelial fenestrations in human CNV (Biesemeier et al, 2014, Schraermeyer et al, 2015. Hofman's group indicated that the vessel leakage was not caused by the fenestration formation, but was due to the increased active pinocytotic vesicles in the endothelia of CNV vessels (Hofman et al, 2000).…”
Section: Overexpression Of Vegf Leads To the Hyperpermeability Of Thesupporting
confidence: 52%
“…Multi-layered basement membranes were often observed around the CNV vessels ( Fig. 4D), which is also a feature of human CNV (Schraermeyer et al, 2015).…”
Section: As Shown In Figs 3 4 the Cnv Induced By Vegf Overexpressiomentioning
confidence: 74%
See 2 more Smart Citations
“…TEM analysis of these pillars and the surrounding vasculature suggests loose tight-junctions and loose connections of the smooth muscle cells to the endothelial cells. As previously described endothelial luminal processes (ELPs) which may take the form of "labyrinth-like" vessels in patients of CNV related wet AMD 188 , are also present in the zebrafish. This suggests that intussuception is likely the process in the human patients for the early expansion of CCs.…”
Section: Discussionmentioning
confidence: 82%